Sabbatical Leave 2018-19 Follow-up Report. - Brownell, Mia (2019)
Two term sabbatical to create "Baroque Float", an extensive number of paintings investigating the visual and conceptual correlation between the structures of life as depicted by scientific molecular/cell imaging and structures of art as depicted by still life and Baroque ceiling painting.
Keywords: dept.art; faculty_collection; sabbatical_report